The Influence of Religious Activities on Students' Study Discipline at SMA Al-Hadiid Cileungsi, Bogor - Fathimah Fathimah; Achmad Junaedi Sitika; Agus Susanto (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study focuses on student learning discipline, with religious activities identified as a contributing factor. The research aims to: 1) Describe students' religious activities at Al-Hadiid High School Cileungsi, 2) Describe their learning discipline, and 3) Analyze the influence of religious activities on learning discipline. Using a correlational method with random sampling, data were collected through questionnaires and documentation. The findings reveal: 1) Students’ religious activities fall into a moderate category (47%), 2) Learning discipline is also in the moderate category (45%), and 3) Religious activities positively influence learning discipline, supported by a normality test (0.200>0.050) and linearity test (0.841>0.050). The regression equation obtained is Y = 17.906 + 0.581X. A correlation coefficient of 0.513 (p = 0.000<0.05) indicates a moderate positive relationship. The t-test result (thitung 4.923>ttabel 1.995) confirms the significant influence of religious activities on learning discipline. The coefficient of determination shows religious activities contribute 26.3% to learning discipline, while 73.7% is influenced by other factors. Thus, the alternative hypothesis (Ha) is accepted, and the null hypothesis (H0) is rejected. Write here the abstract of the article in one paragraph, no more than 200 words. Abstract consists of (1) research objectives, (2) research methods, (3) research conclusions. Other important matters discussed in the paper that significantly contribute to the final results of the research can be noted here, but must consider the limited abstract space.